Fuzzy Distributive Modules - I.M.A. Hadi; Sh. B. Semeein (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2016)
Let R be a commutative ring with unity. In this paper we introduce and study fuzzy distributive modules and fuzzy arithmetical rings as generalizations of (ordinary) distributive modules and arithmetical ring. We give some basic properties about these concepts.